WHISTLEBLOWING AND FINANCIAL FRAUD: A LOOK BACK AT MOTIVATIONS, PROTECTIONS, AND CHALLENGES (A SYSTEMATIC LITERATURE REVIEW) - A. Alyani Achmad; Darwis Said (RADJA PUBLIKA, 2025)
This study aims to review the motivation, protection, and challenges faced by whistleblowers in exposing financial fraud, using the Systematic Literature Review (SLR) approach. This study reviews relevant literature in the period 2005-2025 to identify various factors that influence an individual's decision to report, as well as the effectiveness of the existing reporting system. The results of the study indicate that whistleblower motivation is strongly influenced by a combination of moral, social, and material factors, where moral motivation is often the main driver to report fraud in order to maintain organizational integrity. In addition, financial incentives and legal protection also play an important role in encouraging reporting. Although many countries have adopted whistleblower protection policies, the main challenge is in developing countries, where the implementation of legal protection is often ineffective. This study also found that individual personality and organizational culture also influence the decision to whistleblow. Therefore, this study suggests the need for an improved protection system that is more effective, both in terms of law and organizational culture, to support the success of whistleblowing in preventing financial fraud.